Inadvertent Trypan Blue Staining of Posterior Capsule during Cataract Surgery Associated with “Argentinian Flag” Event - Robert A. Prinzi; Neeti M. Alapati; Shawn S. Gappy; Jason S. Dilly (Case Reports in Ophthalmological Medicine)
Trypan blue is common in visualizing the anterior capsule during cataract surgery. Inadvertent staining of the posterior capsule during phacoemulsification is a rare complication and there are few reports in the literature. The proposed mechanism of posterior capsule staining in previous reports includes a compromised zonular apparatus or iris retractors facilitating the posterior flow of trypan blue. We report the first case of trypan blue staining of the posterior capsule associated with the “Argentinian flag” sign. In our case, the “Argentinian flag” allowed the trypan blue to seep between the posterior capsule and the lens, staining the anterior surface of the posterior capsule.